Fundamentals of strength : principles, experiment, and applications of an internal state variable constitutive formulation - Follansbee, Paul S., 1950- (Hoboken, New Jersey : John Wiley & Sons, 2014)
"Written in a manner that is accessible to both students and practitioners, Fundamentals of Strength discusses the basis and implementation of the Mechanical Threshold Stress (MTS) model. Author P.S. Follansbee, a recognized authority in the field, reviews topics related to mechanical testing, crystal structure, thermodynamics, dislocation motion, dislocation-obstacle interactions, hardening through dislocation accumulation, and deformation kinetics. The text includes an abundance of data and actual model correlations that support the model as well as examples of how the model has been implemented and used to understand the effects of new strengthening mechanisms"--
"The text includes an abundance of data and actual model correlations that support the model as well as examples of how the model has been implemented and used to understand the effects of new strengthening mechanisms"--
Includes index.
Includes bibliographical references at the end of each chapters and index.
Print version record and CIP data provided by publisher.
Keywords: Strength of materials -- Mathematical models; Strains and stresses; TECHNOLOGY & ENGINEERING -- Material Science; SCIENCE -- Mechanics -- General; TECHNOLOGY & ENGINEERING -- Civil -- General; Strains and stresses; Strength of materials -- Mathematical models; Electronic books